A rapid evaluation test method for the long-term storage aging degree of monopropellant decomposition catalyst

Through the thermogravimetric method combining the inert atmosphere and air atmosphere, the oxidation rate of active metal in the single-component propellant decomposition catalyst is accurately measured, and the problem of poor and low repeatability of oxidation rate detection in the prior art is solved, thereby realizing the problem of poor and low repeatability of oxidation rate detection in the prior art. Effective estimates of catalyst activity and lifetime.

CN119147409BActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411605139.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The prior art is difficult to accurately detect the oxidation rates of active metals iridium and ruthenium in a single-component propellant decomposition catalyst, resulting in a decrease in catalyst activity and failure.

Method used

The thermogravimetric test method combined with an inert atmosphere and an air atmosphere is used to calculate the mass of the metal that has not been oxidized in the catalyst by measuring the complete oxidation weight gain of the active metal, thereby calculating the oxidation rate of the catalyst active metal.

Benefits of technology

The rapid, simple and accurate determination of the oxidation rate of the catalyst active metal is achieved, and the estimated requirements for long-storage catalyst activity and life are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147409B_ABST
    Figure CN119147409B_ABST
Patent Text Reader

Abstract

The present invention provides a rapid evaluation test method for the long-term storage aging degree of a monocomponent propellant decomposition catalyst, which belongs to the field of aerospace catalyst technology and is mainly used for detecting the oxidation rate of active metals iridium and ruthenium in monocomponent propellant decomposition catalysts. The present invention designs a rapid thermogravimetric evaluation method, which measures the weight gain of the active metal after complete oxidation, calculates the mass of the unoxidized metal, and thus calculates the oxidation rate of the active metal of the catalyst. The measurement of the present invention is fast and simple, with good repeatability. The test of a single sample only takes about three hours. It can effectively detect and calculate the oxidation degree of the active metal of the catalyst, provide an effective basis for determining the activity of the catalyst, and effectively meet the demand for estimating the activity and life of the long-term catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerospace catalysts, and relates to a rapid evaluation test method for the long-term storage aging degree of a monopropellant decomposition catalyst, which is mainly used for detecting the oxidation rate of active metals iridium and ruthenium in the monopropellant decomposition catalyst. Background Art

[0002] The monopropellant propulsion system has the advantages of simple structure, sensitive response characteristics, and high working reliability, so it has become the preferred technical solution for equipment end-of-life power. Monopropellant propulsion technology has a wide range of applications in aerospace, defense and other fields.

[0003] However, as the storage time of the catalyst product increases, the performance of the catalyst will degrade to a certain extent, and even fail. Monocomponent propellant decomposition catalysts are a type of composite inorganic materials with fixed shapes and special functions. They are composed of carriers and active metals. The carrier is mainly porous alumina, and the main components of the active metals are precious metals such as Ir and Ru. After a special preparation method, the active metals are highly dispersed on the surface and pores of the carrier at the nanoscale. Unlike single precious metals, nanoscale dispersed active metals are more active in nature, so they show high catalytic activity. At the same time, some storage conditions during long-term storage may also have a certain impact on their lifespan. Studies have found that highly dispersed active metals will gradually be oxidized by oxygen in the air during long-term storage, resulting in an increase in the oxidation rate of the active metals in the catalyst, resulting in a decrease in activity. The oxidation rate is a key factor affecting the activity of the catalyst, and relatively accurate measurements are required to make a preliminary judgment on the current activity of the catalyst.

[0004] The main test method at present is the H2-TPR test method, which uses H2 to reduce the catalyst and measure the H2 consumption to determine the oxidation degree of the catalyst. However, it is found in the study that its repeatability is poor, and some deeply oxidized metals cannot be completely reduced, making the measured oxidation rate low. The present invention adopts thermogravimetry to measure the weight gain of the active metal after complete oxidation, calculate the mass of the unoxidized metal, and thus calculate the oxidation rate of the active metal of the catalyst. The measurement is fast, simple, and has good repeatability, which can provide an effective basis for determining the activity of the catalyst. Summary of the invention

[0005] In order to accurately measure the oxidation rates of active metals iridium and ruthenium in a monopropellant decomposition catalyst and determine the catalyst activity, the present invention provides a rapid evaluation test method for the long-term storage aging degree of a monopropellant decomposition catalyst.

[0006] In order to achieve the above technical tasks, the present invention adopts the following technical solutions:

[0007] A rapid evaluation test method for the long-term storage aging degree of a monopropellant decomposition catalyst comprises the following steps:

[0008] Step 1, according to the range of the thermogravimetric instrument, weigh 0.1g~1g of the catalyst sample into a crucible, pass an inert gas at a flow rate of 100mL / min~300mL / min, purge for 30min~2h, completely replace the atmosphere in the thermogravimetric instrument with an inert atmosphere, and heat up to 350~550°C at a heating rate of 2~20°C / min, keep the temperature constant for 10min~1h, and obtain the thermogravimetric test results under the inert atmosphere; then replace the inert atmosphere with air at a flow rate of 100mL / min~300mL / min, keep the temperature constant for 30min~2h, and obtain the thermogravimetric test results under the air atmosphere.

[0009] Furthermore, the catalyst is a monocomponent propellant decomposition catalyst, including an Ir catalyst and a Ru catalyst.

[0010] Step 2, read the following data from the thermogravimetric test results obtained in step 1:

[0011] The lowest value of the mass fraction at constant temperature in an inert atmosphere between 350°C and 550°C is recorded as ω1;

[0012] The highest value of the mass fraction at a constant temperature of 350°C to 550°C in an air atmosphere is recorded as ω2.

[0013] The weight gain mass fraction of the unoxidized metal in the catalyst is calculated by the following formula:

[0014] ω = (ω2-ω1) / ω1

[0015] Wherein: ω is the mass fraction of the unoxidized metal weight gain in the catalyst; ω1 is the mass fraction of the lowest value at a constant temperature of 350°C~550°C in an inert atmosphere; ω2 is the mass fraction of the highest value at a constant temperature of 350°C~550°C in an air atmosphere.

[0016] The mass fractions of Ru and Ir metal contents in the catalyst are known, denoted as ω Ru and ω Ir When the Ir catalyst is completely oxidized, it can be considered that all of it generates IrO2, and the mass fraction of Ir gain is recorded as ω Ir-O2 ; When the Ru catalyst is completely oxidized, it can be considered that all of it generates RuO2, and the Ru weight gain mass fraction is ω Ru-O2 .

[0017] The Ir weight gain mass fraction ω Ir-O2 Calculated by the following formula:

[0018] ω Ir-O2 = ωIr / M Ir ×M O ×2

[0019] Where: Ir-O2 is the mass fraction of Ir catalyst completely oxidized; ω Ir is the mass fraction of the metal content in the Ir catalyst; M Ir is the atomic mass of iridium, g / mol; M O is the atomic mass of oxygen, g / mol.

[0020] The Ru weight gain mass fraction ω Ru-O2 Calculated by the following formula:

[0021] ω Ru-O2 = ω Ru / M Ru ×M O ×2

[0022] Where: Ru-O2 is the mass fraction of Ru catalyst completely oxidized; ω Ru is the mass fraction of the metal content in the Ru catalyst; M Ru is the atomic mass of iridium, g / mol; M O is the atomic mass of oxygen, g / mol.

[0023] The oxidation rate of the metal in the Ir catalyst is calculated by the following method:

[0024] X = [(1+ω) / (1+ω) Ir-O2 )×ω Ir-O2 -ω)] / [(1+ω) / (1+ω Ir-O2 )×ω Ir-O2 ]×100%.

[0025] The oxidation rate of the metal in the Ru catalyst is calculated by the following method:

[0026] X = [(1+ω) / (1+ω) Ru-O2 )×ω Ru-O2 -ω)] / [(1+ω) / (1+ω Ru-O2 )×ω Ru-O2 ]×100%.

[0027] For the Ir catalyst, the temperature when the atmosphere is air is 450°C~550°C, preferably 500°C; for the Ru catalyst, the temperature when the atmosphere is air is 350°C~450°C, preferably 400°C.

[0028] The beneficial effects of the present invention are:

[0029] Aiming at detecting the degree of aging of monopropellant decomposition catalysts during long-term storage, the present invention designs a rapid thermogravimetric evaluation method. The test of a single sample only takes about 3 hours, and the degree of oxidation of active metals in the catalyst can be effectively detected and calculated, which can effectively meet the demand for estimating the activity and life of long-term storage catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the thermogravimetric test data of the newly prepared Ru catalyst in Example 1.

[0031] Figure 2 This is a graph showing the thermogravimetric test data of the Ru catalyst stored for about 3 years in Example 2.

[0032] Figure 3 This is the thermogravimetric test data diagram of the newly prepared Ir catalyst in Example 2.

[0033] Figure 4 This is a graph showing the thermogravimetric test data of the Ir catalyst stored for about 10 years in Example 2. DETAILED DESCRIPTION

[0034] The following are examples to further illustrate the present invention:

[0035] Embodiment 1:

[0036] The test sample is a Ru / Al2O3 catalyst material with a Ru content of 24%. The weight gain mass fraction ω of the catalyst after complete oxidation of Ru is calculated. Ru-O2 It is 7.60%.

[0037] The thermogravimetric test procedure was as follows: Ar atmosphere gas flow rate 300 mL / min, purge for 1 h, heating rate 5 °C / min, heating to 400 °C, constant temperature for 10 min, changing the atmosphere to air 100 mL / min, constant temperature for 30 min.

[0038] Figure 1 The thermogravimetric test data of the catalyst material is shown in FIG. 1 , where the lowest value of the inert atmosphere mass fraction ω1 is 98.54%, the highest value of the air atmosphere mass fraction ω2 is 103.16%, and the weight gain mass fraction of the unoxidized metal in the Ru catalyst is:

[0039] ω = (ω2-ω1) / ω1 = 4.6885%

[0040] The oxidation rate of the metal in the Ru catalyst was calculated as:

[0041] X = [(1+ω) / (1+ω) Ru-O2 )×ω Ru-O2 -ω)] / [(1+ω) / (1+ω Ru-O2 )×ω Ru-O2]×100% =36.59%

[0042] Finally, the oxidation rate of metal in the Ru catalyst was detected to be 36.59%.

[0043] Embodiment 2:

[0044] The Ru / Al2O3 catalyst material stored for about 3 years has a Ru content of 24%. Calculate the weight gain mass fraction ω after the Ru in the catalyst is completely oxidized. Ru-O2 It is 7.60%.

[0045] The thermogravimetric test procedure was as follows: Ar atmosphere gas flow rate 300 mL / min, purge for 1 h, heating rate 5 °C / min, heating to 400 °C, constant temperature for 10 min, changing the atmosphere to air 100 mL / min, constant temperature for 1 h.

[0046] Figure 2 The thermogravimetric test data of the catalyst material is shown in FIG. 1 , where the lowest value of the inert atmosphere mass fraction ω1 is 92.23%, the highest value of the air atmosphere mass fraction ω2 is 95.38%, and the weight gain mass fraction of the unoxidized metal in the Ru catalyst is:

[0047] ω = (ω2-ω1) / ω1 = 3.4154%

[0048] The oxidation rate of the metal in the Ru catalyst was calculated as:

[0049] X = [(1+ω) / (1+ω) Ru-O2 )×ω Ru-O2 -ω)] / [(1+ω) / (1+ω Ru-O2 )×ω Ru-O2 ]×100% =53.24%

[0050] Finally, the oxidation rate of the metal in the Ru catalyst was detected to be 53.24%. It can be observed that the metal oxidation rate increased significantly with the increase of storage time.

[0051] Embodiment 3:

[0052] The test sample is Ir / Al2O3 catalyst material, in which the Ir content is 17%. Calculate the weight gain mass fraction ω after the Ir in the catalyst is completely oxidized. Ru-O2 It is 2.83%.

[0053] The thermogravimetric test procedure was as follows: Ar atmosphere gas flow rate 300 mL / min, purge for 1 h, heating rate 5 °C / min, heating to 500 °C, constant temperature for 10 min, changing the atmosphere to air 100 mL / min, constant temperature for 60 min.

[0054] Figure 3The thermogravimetric test data of the catalyst material is shown in FIG. 1 , where the lowest value of the inert atmosphere mass fraction ω1 is 97.42%, the highest value of the air atmosphere mass fraction ω2 is 98.84%, and the weight gain mass fraction of the unoxidized metal in the Ir catalyst is:

[0055] ω = (ω2-ω1) / ω1 = 1.4576%

[0056] The oxidation rate of the metal in the Ir catalyst was calculated as:

[0057] X = [(1+ω) / (1+ω) Ir-O2 )×ω Ir-O2 -ω)] / [(1+ω) / (1+ω Ir-O2 )×ω Ir-O2 ]×100%=47.78%

[0058] Finally, it was detected that the oxidation rate of the metal in the newly prepared Ir catalyst was 47.78%.

[0059] Embodiment 4:

[0060] The test sample is an Ir / Al2O3 catalyst material stored for about 10 years, in which the Ir content is 17%. The weight gain mass fraction ω of the catalyst after the Ir is completely oxidized is calculated. Ru-O2 It is 2.83%.

[0061] The thermogravimetric test procedure was as follows: Ar atmosphere gas flow rate 300 mL / min, purge for 1 h, heating rate 5 °C / min, heating to 500 °C, constant temperature for 10 min, changing the atmosphere to air 100 mL / min, constant temperature for 60 min.

[0062] Figure 4 The thermogravimetric test data of the catalyst material is shown in FIG. 1 , where the lowest value of the inert atmosphere mass fraction ω1 is 93.05%, the highest value of the air atmosphere mass fraction ω2 is 94.30%, and the weight gain mass fraction of the unoxidized metal in the Ir catalyst is:

[0063] ω = (ω2-ω1) / ω1 = 1.3434%

[0064] The oxidation rate of the metal in the Ir catalyst was calculated as:

[0065] X = [(1+ω) / (1+ω) Ir-O2 )×ω Ir-O2 -ω)] / [(1+ω) / (1+ω Ir-O2 )×ω Ir-O2 ]×100%=51.83%

[0066] Finally, it was detected that the metal oxidation rate in the Ir catalyst stored for 10 years was 51.83%. It can be observed that with the increase of storage time, the metal oxidation rate increased to a certain extent.

[0067] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for rapidly evaluating the long-term storage aging degree of a monopropellant decomposition catalyst, wherein the catalyst is a monopropellant decomposition catalyst, including an Ir catalyst and a Ru catalyst, characterized in that: The method for rapidly evaluating the long-term storage aging degree of a monopropellant decomposition catalyst comprises the following steps: Step 1, according to the range of the thermogravimetric instrument, weigh 0.1g~1g of the catalyst sample into a crucible, pass an inert gas, completely replace the atmosphere in the thermogravimetric instrument with an inert atmosphere, heat to 350~550°C, keep constant temperature for 10min~1h, and obtain the thermogravimetric test results under the inert atmosphere; replace the inert gas with air, the flow rate is 100mL / min~300mL / min, keep constant temperature for 30min~2h, and obtain the thermogravimetric test results under air atmosphere; Step 2, read the following data from the thermogravimetric test results obtained in step 1: The lowest value of the mass fraction at constant temperature in an inert atmosphere between 350°C and 550°C is recorded as ω1; The highest value of the mass fraction at constant temperature in air atmosphere between 350°C and 550°C is recorded as ω2; The weight gain mass fraction of the unoxidized metal in the catalyst is calculated by the following formula: ω = (ω2-ω1) / ω1 Where: ω is the mass fraction of the unoxidized metal weight gain in the catalyst; ω1 is the mass fraction of the lowest value at a constant temperature of 350°C to 550°C in an inert atmosphere; ω2 is the mass fraction of the highest value at a constant temperature of 350°C to 550°C in an air atmosphere; The mass fractions of Ru and Ir metal contents in the catalyst are known, denoted as ω Ru and ω Ir When the Ir catalyst is completely oxidized, it is considered to generate all IrO2, and the mass fraction of Ir gain is recorded as ω Ir-O2 ; When the Ru catalyst is completely oxidized, it is considered that all of it generates RuO2, and the Ru weight gain is ω Ru-O2 ; The Ir weight gain mass fraction ω Ir-O2 Calculated by the following formula: oh Ir-O2 = ω Ir / M Ir ×M O ×2 Where: Ir-O2 is the mass fraction of Ir catalyst completely oxidized; ω Ir is the mass fraction of the metal content in the Ir catalyst; M Ir is the atomic mass of iridium, g / mol; M O is the atomic mass of oxygen, g / mol; The Ru weight gain mass fraction ω Ru-O2 Calculated by the following formula: oh Ru-O2 = ω Ru / M Ru ×M O ×2 Where: Ru-O2 is the mass fraction of Ru catalyst completely oxidized; ω Ru is the mass fraction of metal content in Ru catalyst; M Ru is the atomic mass of iridium, g / mol; M O is the atomic mass of oxygen, g / mol; The oxidation rate of the metal in the Ir catalyst is calculated by the following method: X = [(1+ω) / (1+ω) Ir-O2 )×ω Ir-O2 -ω)] / [(1+ω) / (1+ω) Ir-O2 )×ω Ir-O2 ]×100%; The oxidation rate of the metal in the Ru catalyst is calculated by the following method: X = [(1+ω) / (1+ω) Ru-O2 )×ω Ru-O2 -ω)] / [(1+ω) / (1+ω) Ru-O2 )×ω Ru-O2 ]×100%.

2. The method for rapid evaluation of the long-term storage aging degree of a monopropellant decomposition catalyst according to claim 1, characterized in that: In the step 1, the flow rate of the inert gas is 100 mL / min~300 mL / min, the purge time is 30 min~2 h, and the heating rate under the inert atmosphere is 2~20 ° C / min.

3. The method for rapid evaluation of the long-term storage aging degree of a monopropellant decomposition catalyst according to claim 1, characterized in that: In the step 1, the flow rate of air is 100 mL / min to 300 mL / min, and the purge time is 30 min to 2 h.

4. The method for rapid evaluation of the long-term storage aging degree of a monopropellant decomposition catalyst according to claim 1, characterized in that: For the Ir catalyst, the temperature when the atmosphere is air is 450°C~550°C.

5. A rapid evaluation test method for the long-term storage aging degree of a monopropellant decomposition catalyst according to claim 4, characterized in that: For the Ir catalyst, the temperature was 500°C when the atmosphere was air.

6. The method for rapid evaluation of the long-term storage aging degree of a monopropellant decomposition catalyst according to claim 1, characterized in that: For the Ru catalyst, the temperature is 350°C~450°C when the atmosphere is air.

7. A rapid evaluation test method for the long-term storage aging degree of a monopropellant decomposition catalyst according to claim 6, characterized in that: For the Ru catalyst, the temperature was 400°C when the atmosphere was air.

Citation Information

Patent Citations

  • Method for quantitatively detecting surfactant in nano-catalyst

    CN112986040A

  • Propellant catalytic decomposition performance evaluation device

    CN210626410U